Discursive strategies and speech acts in political discourse of Najib and Modi - Ramanathan, Renugah; Paramasivam, Shamala; Tan, Bee Hoon (Shanlax International Journals, 2020)
Election campaigns are constantly regarded as a persuasive campaign to convince the nation to vote for the leader of a country. Being said such, this study investigates the discourse of twitter of two political premiers in Asia: Former Prime Minister of Malaysia, Najib Tun Razak (henceforth, Najib) and Prime Minister Narendra Modi (henceforth, Modi), in the aspects of discursive strategies and speech acts during election campaigns. The discourse of Najib and Modi are selected due to their active participation on Twitter throughout election campaigns. The data were collected over 3 months throughout the national elections of both the countries, which were from February to April 2013 in Malaysia and January to March 2014 in India. This qualitative study employs Wodak's discursive strategies to analyze the lexical choices utilized in the election tweets and Searle's speech act taxonomy to analyze the speech acts used. The presence of two major speech acts was highlighted during the elections: commissives and directives. These two speech acts collaborated under the hood of discursive strategies of predication and perspectivation that empowered Najib and Modi to establish a strong contact with citizens while creating a sense of integrity and oneness. This study is significant as it creates political and language awareness to citizens by denoting how political figures establish power through mutual consent with citizens using Twitter. Furthermore, this study enlightens citizens on how the 140-character tool can influence the political decision-making of a community.